EVALUASI APLIKASI GOOGLE CLASSROOM MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) PADA UNIVERSITAS ISLAM INDRAGIRI - Halimatussa’diah; Samsudin (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
Indragiri Islamic University is committed to utilizing technology and information systems to support online learning and create a smart campus ecosystem. Although Google Classroom does not fully meet certain e-learning standards, in practice, this application is often used in academic environments. Research using the System Usability Scale (SUS) shows that in general, Google Classroom receives positive assessments from users. In terms of application acceptance (Acceptability), this application is categorized as